Pengaruh Pemahaman Peran Gender terhadap Social Loafing: Studi Pada Organisasi Kemahasiswaan BLM FKIP Universitas Siliwangi Periode Tahun 2023 - Nisya, Mutiara; Herwina, Wiwin; Karwati, Lilis (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Social loafing is a phenomenon that shows a decrease in individual performance when faced with work in groups. Social loafing can occur in both men and women, both adolescents and adults. This study aims to determine the effect of understanding gender roles on social loafing. The method used in this study is a quantitative approach with the type of primary research. The results of the hypothesis test of simple linear regression analysis in this study showed significant results of 0.002 this value < 0.005 (5%) and the value of the regression coefficient (b) of the gender role understanding variable is -0.066 where the negative sign (-) indicates the direction of the relationship that is not in the same direction, so it can be concluded that H₀ is rejected, then in understanding gender roles has a significant effect on social loafing. The results of the determination analysis test (R-Square) value of the contribution of understanding gender roles to social loafing was 28.5%. So it can be concluded that the results of this study show a significant and negative influence, where if the level of understanding of gender roles is high, the level of social loafing is low, and vice versa.